Arp2/3 complex- and formin-mediated actin cytoskeleton networks facilitate actin binding protein sorting in fission yeast - Kaitlin E. Homa; Glen M. Hocky; Cristian Suarez; David R. Kovar (European Journal of Cell Biology, 2024)
While it is well-established that F-actin networks with specific organizations and dynamics are tightly regulated by distinct sets of associated actin-binding proteins (ABPs), how ABPs self-sort to particular F-actin networks remains largely unclear. We report that actin assembly factors Arp2/3 complex and formin Cdc12 tune the association of ABPs fimbrin Fim1 and tropomyosin Cdc8 to different F-actin networks in fission yeast. Genetic and pharmacological disruption of F-actin networks revealed that Fim1 is preferentially directed to Arp2/3-complex mediated actin patches, whereas Cdc8 is preferentially targeted to formin Cdc12-mediated filaments in the contractile ring. To investigate the role of Arp2/3 complex- and formin Cdc12-mediated actin assembly, we used four-color TIRF microscopy to observe the in vitro reconstitution of ABP sorting with purified proteins. Fim1 or Cdc8 alone bind similarly well to filaments assembled by either assembly factor. However, in ‘competition’ reactions containing both actin assembly factors and both ABPs, ∼2.0-fold more Fim1 and ∼3.5-fold more Cdc8 accumulates on Arp2/3 complex branch points and formin Cdc12-assembled actin filaments, respectively. These findings indicate that F-actin assembly factors Arp2/3 complex and formin Cdc12 help facilitate the recruitment of specific ABPs, thereby tuning ABP sorting and subsequently establishing the identity of F-actin networks in fission yeast.